Understanding capacities to scale innovations for sustainable development: a learning journey of scaling partnerships in three parts of Africa - Wigboldus, Seerp; McEwan, M.A.; Schagen, Boudy van; Okike, Iheanacho; Mourik, Tom A. van; Rietveld, Anne M.; Amole, Tunde A.; Asfaw, F.; Hundayehu, M.C.; Iradukunda, Francois; Kulakow, Peter A.; Namanda, S.; et al. (Springer, 2023)
Finding out how to scale innovations successfully is high on the agendas of researchers, practitioners and policy makers involved in agricultural development. New approaches and methodologies seek to better address related complexities, but none of them include a systematic perspective on the role of capacity in (partnerships for) scaling innovations. We posit that this has left an important topic insufficiently addressed in relation to partnerships for scaling innovations. The need to address this gap became apparent in the context of the CGIAR Roots, Tubers, and Bananas (RTB) Scaling Fund initiative. This paper presents how we explored ways forward in relation to this by combining three methodological approaches: The Five-Capabilities, Scaling Readiness, and the Multi-Level Perspective on socio-technical innovation. This combined approach—dubbed Capacity for Scaling Innovations (C4SI)—was applied in three projects related to scaling innovations for sweet potato, cassava and banana, involving five countries in Africa. It then discusses implications for a partners-in-scaling perspective, the contribution of scaling innovations to sustainable development, the importance of research organisations considering their own capabilities in partnerships for scaling, and the extent to which C4SI was helpful in the three cases—for example, in decision making. The paper concludes that a capacity perspective on the scaling of innovations should be an essential part of a ‘science of scaling’. Finally, it provides recommendations for using the approach or parts of it in research and intervention practice for scaling, pointing in particular to the need for context-specific adaptation.